Electrochemical generation of sulfur vacancies in the basal plane of MoS2 for hydrogen evolution - Tsai, Charlie (2018)
Recently, sulfur (S)-vacancies created on the basal plane of 2H-molybdenum disulfide (MoS2) using argon plasma exposure exhibited higher intrinsic activity for the electrochemical hydrogen evolution reaction than the edge sites and metallic 1T-phase of MoS2 catalysts. However, a more industrially viable alternative to the argon plasma desulfurization process is needed. In this work, we introduce a scalable route towards generating S-vacancies on the MoS2 basal plane using electrochemical desulfurization. Even though sulfur atoms on the basal plane are known to be stable and inert, we find that they can be electrochemically reduced under accessible applied potentials. This can be done on various 2H-MoS2 nanostructures. By changing the applied desulfurization potential, the extent of desulfurization and the resulting activity can be varied. The resulting active sites are stable under extended desulfurization durations and show consistent HER activity.